TRANSFORMING INFORMATION SECURITY optimizing five concurrent trends to reduce resource drain. - MORIARTY, KATHLEEN M. (EMERALD GROUP PUBL, 2020)
Providing a unique perspective from the center of the debates on end-to-end encryption, Moriarty explores emerging trends in both information security and transport protocol evolution, going beyond simply pointing out today's problems to providing solutions for the future of our product space.